A new approach to assessing carbon fiber/epoxy interfacial shear strength by tensile test of 45° fiber bundle composites: Experiment, modeling and applicability. (6th June 2016) - Qi, Guocheng; Du, Shanyi; Zhang, Boming; Yu, Yalin
Abstract: This work concentrates on the assessment of carbon fiber/epoxy interfacial shear strength by 45° fiber bundle tensile (45FBT) test. The 45FBT samples for three different carbon fiber/epoxy systems were prepared and tested. The multiscale model based on the generalized methods of cells (GMC) was established to simulate the tensile damage process and analyze the interfacial stress state. The interfacial shear strength in 45FBT specimen was calculated. The 45FBT test was compared with the transverse fiber bundle tensile (TFBT) test. The applicability of the 45FBT test was finally discussed.